Elżbieta Maria Umińska-Tytoń – in the circle of the name and surname of the jubilarian - Marciniak-Firadza, Renata (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The aim of the article is primarily to present the etymology of the names and surnames of the Jubilarian as well as the way these onimas function both historically and today. The source material for analysis was excerpted from dictionaries of the Polish language: etymological, general (explanatory: historical and contemporary dictionaries), dialect, phraseological, and onomastic.